Rapid, sensitive, and specific immunomagnetic separation of foodborne pathogens. (19th September 2011) - Setterington, Emma B.; Cloutier, Barbara C.; Ochoa, Jessica M.; Cloutier, Ashley K.; Patel, Parul J.; Alocilja, Evangelyn C.
Food defence requires the means to efficiently screen large volumes of food for microbial pathogens. Even rapid detection methods often require lengthy enrichment steps, making them impractical for this application. There is a great need for rapid, sensitive, specific, and inexpensive methods for extracting and concentrating microbial pathogens from food. In this study, an immunomagnetic separation (IMS) methodology was developed for Escherichia coli O157:H7, using three different types of magnetic nanoparticles (MNPs). The microbiological specificity of the IMS method was evaluated against Escherichia coli O55:H7 and Shigella boydii, and was improved by addition of NaCl during conjugation of antibodies onto MNPs. The microbiological sensitivity of the IMS method was greatest when a high concentration of antibodies (1.0 mg/ml) was present during conjugation. MNP concentrations of 1.0 mg/ml and 0.5 mg/ml provided optimal sensitivity and specificity. The entire IMS procedure requires only 35 minutes, and antibody-conjugated MNPs show no decline in performance up to 60 days after conjugation.